Women in Contemporary Latin American Novels Psychoanalysis and Gendered Violence (Literatures of the Americas, 2018)
This book explores the relationship between psychoanalysis, literary criticism and contemporary literature. Focusing on Latin America, and using examples from Brazilian, Colombian, Chilean, Puerto Rican, and Mexican literature, it provides an important account of why gendered violence occurs and how it is portrayed. In the novels discussed, the protagonists express similar fears, passions and illnesses that are present in contemporary Latin America. Psychoanalysis and literary criticism offer us an interpretative framework to understand these voices, especially those that are in the margin. Women, particularly, as part of a globalized labor force, express through their bodies social problems that range from the erotic use of the body in a hypersexualized world, to the body as a receptacle of violence that expresses the death drive. This book is a fascinating contribution to literary, gender, and cultural studies.